Development of 3D-iNET ORION: a novel, pre-clinical, three-dimensional in vitro cell model for modeling human metastatic neuroendocrine tumor of the pancreas - Jan Strnadel; Mark A. Valasek; Grace Y. Lin; Huahui Lin; Ann M. Ponsford Tipps; Sang Myung Woo; Ken Fujimura; Huawei Wang; Sunkyu Choi; Jack Bui; Christopher Hermosillo; Kristen Jepsen; et al. (Human Cell, 2024)
Neuroendocrine tumors (NETs) of the pancreas are rare neoplasms that present complex challenges to diagnosis and treatment due to their indolent course. The incidence of pancreatic neuroendocrine tumors has increased significantly over the past two decades. A limited number of pancreatic neuroendocrine cell lines are currently available for the research. Here, we present 3D-iNET ORION, a novel 3-dimensional (spheroid) cell line, isolated from human pancreatic neuroendocrine tumor liver metastasis. Three-dimensionally grown (3D) cancer cell lines have gained interest over the past years as 3D cancer cell lines better recapitulate the in vivo structure of tumors, and are more suitable for in vitro and in vivo experiments. 3D-iNET ORION cancer cell line showed high potential to form tumorspheres when embedded in Matrigel matrix and expresses synaptophysin and EpCAM. Electron microscopy analysis of cancer cell line proved the presence of dense neurosecretory granules. When xenografted into athymic mice, 3D-iNET ORION cells produce slow-growing tumors, positive for chromogranin and synaptophysin. Human Core Exome Panel Analysis has shown that 3DiNET ORION cell line retains the genetic aberration profile detected in the original tumor. In conclusion, our newly developed neuroendocrine cancer cell line can be considered as a new research tool for in vitro and in vivo experiments.

Mortality risk factors and fulminant sub-phenotype in anaerobic bacteremia: a 10-year retrospective, multicenter, observational cohort study - Kentaro Nagaoka; N. Iwanaga; Y. Takegoshi; Y. Murai; H. Kawasuji; M. Miura; Y. Sato; Y. Hatakeyama; H. Ito; Y. Kato; N. Shibayama; Y. Terasaki; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Sialyl-glycoconjugates in cholesterol-rich microdomains of P388 cells are the triggers for apoptosis induced by Rana catesbeiana oocyte ribonuclease - Y. Ogawa; S. Sugawara; T. Tatsuta; M. Hosono; K. Nitta; Y. Fujii; H. Kobayashi; T. Fujimura; H. Taka; Y. Koide; I. Hasan; R. Matsumoto; et al. (Glycoconjugate Journal, 2014)

Biological and chemical characteristics of the coral gastric cavity - S. Agostini; Y. Suzuki; T. Higuchi; B. E. Casareto; K. Yoshinaga; Y. Nakano; H. Fujimura (Coral Reefs, 2012)

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Positional cloning of the rice Rf-1 gene, a restorer of BT-type cytoplasmic male sterility that encodes a mitochondria-targeting PPR protein - H. Akagi; A. Nakamura; Y. Yokozeki-Misono; A. Inagaki; H. Takahashi; K. Mori; T. Fujimura (Theoretical and Applied Genetics, 2004)

Mapping QTLs influencing rice floral morphology using recombinant inbred lines derived from a cross between Oryza sativa L. and Oryza rufipogon Griff. - Y. Uga; Y. Fukuta; H. W. Cai; H. Iwata; R. Ohsawa; H. Morishima; T. Fujimura (Theoretical and Applied Genetics, 2003)

Mapping QTLs influencing rice floral morphology using recombinant inbred lines derived from a cross between Oryza sativa L. and Oryza rufipogon Griff - Y. Uga; Y. Fukuta; H. W. Cai; H. Iwata; R. Ohsawa; H. Morishima; T. Fujimura (Theoretical and Applied Genetics, 2003)

Micron, a microsatellite-targeting transposable element in the rice genome - H. Akagi; Y. Yokozeki; A. Inagaki; K. Mori; T. Fujimura (Molecular Genetics and Genomics, 2001)

Lack of kinetic interaction between digoxin and voglibose - M. Kusumoto; K. Ueno; Y. Fujimura; T. Kameda; K. Mashimo; K. Takeda; R. Tatami; M. Shibakawa (European Journal of Clinical Pharmacology, 1999)

Effects of dopamine on veins in humans: comparison with noradrenaline and influence of age - K. Harada; M. Ohmori; Y. Kito; A. Fujimura (European Journal of Clinical Pharmacology, 1998)

Highly polymorphic microsatellites of rice consist of AT repeats, and a classification of closely related cultivars with these microsatellite loci - H. Akagi; Y. Yokozeki; A. Inagaki; T. Fujimura (Theoretical and Applied Genetics, 1997)